Restoration performance of Thalassia hemprichii and Enhalus acoroides at Gaolong bay and Xincun lagoon, Hainan Island, China - Shen, Jie; Yin, Lei; Zhang, Jian; Jia, Shuwen; Wang, Yi; Wang, Daoru; Cai, Zefu; Chen, Shiquan (Frontiers in Marine Science, 2023)
Introduction Seagrasses play a key role in biodiversity maintenance, sediment stabilization, and carbon reduction. Due to the significant decline of seagrass populations worldwide, many projects to restore seagrass by transplantation have been undertaken in recent decades. However, effective restoration technologies required to rapidly restore seagrass on Hainan Island are yet to be developed. Methods In this study, an experiment was carried out to investigate methods for alleviating continuous degradation of seagrass beds on Hainan Island. Seagrass were transplanted by “single-plant-fixed-distance transplantation” method, survival rate, shoot formation rate, coverage and shoot density of transplanting plants were monitored for 23 months. Results Over 67% of T. hemprichii and 90% of E. acoroides were still alive, shoot density were over 11 shoots/m2 and 15 shoots/m2 respectively after almost two years, E. acoroides was more likely to survive than T. hemprichii both in Gaolong Bay and Xincun lagoon. Because of the damage to below-ground tissues, the survival rate, shoot formation rate, coverage and shoot density decreased during the first one year after transplantation, then increased gradually. Discussion We considered transplantation established successfully of T. hemprichii and E. acoroides in the new site was about 12 months. In addition, T. hemprichii was suitable for transplanted in Xincun lagoon, and E. acoroides was suitable for transplanted in Gaolong bay. The results demonstrated that the growth of transplanted seagrass was greatly affected by suspend solids and DIN. The results of this study may provide data support and scientific basis for seagrass transplantation in South China.